Finapres arterial pulse wave analysis with Modelflow® is not a reliable non-invasive method for assessment of cardiac output - REMMEN, Jaap J.; AENGEVAEREN, Wim R.M.; VERHEUGT, Freek W.A.; VAN DER WERF, Tjeerd; LUIJTEN, Hans E.; BOS, Anja; JANSEN, René W.M.M. (Clinical science (1979), 2002)
Non-invasive continuous monitoring of cardiac output could be very useful in clinical care and in research settings, particularly in elderly subjects. We studied whether Finapres arterial pulse wave analysis with Modelflow® is a reliable non-invasive method for the assessment of cardiac output in healthy elderly subjects. We compared Modelflow® cardiac output (MFCO) with thermodilution cardiac output (TDCO) in 28 healthy subjects, aged 70±4years (mean±S.D.). TDCO was measured during right-sided heart catheterization, while MFCO was calculated with Modelflow® software from non-invasive arterial Finapres blood pressure, which was measured simultaneously. The two methods were compared using a paired t-test, by Pearson correlation, and by Bland–Altman analysis. TDCO was 6.4±1.1litres/min (mean±S.D.) and MFCO was 4.7±1.3litres/min (P<0.001). There was no significant correlation between MFCO and TDCO (r = 0.28, P = 0.13). Mean difference (bias) was -1.7litres/min (S.E.M. 0.27litres/min), with an S.D. (precision) of 1.5litres/min. The 95% limits of agreement were -4.6 to +1.1litres/min. In conclusion, non-invasive MFCO values differed significantly from and showed no significant correlation with invasively determined TDCO values in the normal range. Although simple, non-invasive and patient-friendly, the Modelflow® method is inaccurate for assessment of cardiac output without invasive calibration.